PLP DASAR SEBAGAI KUNCI ALTERNATIF PENGENALAN LINGKUNGAN SEKOLAH DI SEKOLAH DASAR INPRES PARANG BERU - Syamsinar; Ratnawati (Jurnal Riset Guru Indonesia, 2024)
In the FKIP Unismuh Makassar environment, the introduction to the school field program (PLP) aims: (1) Building a foundation for educator identity and strengthening educational academic potential and (2) Forming and improving student competence in aspects of attitude, knowledge, and skills as prospective educators. The implementation of this PLP uses a qualitative description method carried out with a block system which is taken for 16 days, 4 days on campus and 12 days at school with an implementation time of 5 hours 40 minutes per day. Based on the results of direct observation, it shows that the discipline of school residents has been implemented well, the relationship between school residents is good. However, the relationship between students and students needs to be given direction so that students behave well with each other. The school practices and habits have been implemented well with the introduction of the school field at SD INPRES PARANG BERU, practitioners can find out the school profile, school management, culture, and school culture, strengthening character education, as well as observing co-curricular activities, curricular and observing extracurricular activities.